Epigenetic factors as drivers of fibrosis in systemic sclerosis - Bergmann, Christina; Distler, Jörg (Epigenomics, 2017)
Prolonged activation of fibroblasts is a central hallmark of fibrosing disorders such as systemic sclerosis (SSc). Fibroblasts are the key effector cells. They differentiate into an activated myofibroblast phenotype. In contrast to normal wound healing with transient activation, myofibroblasts persist in fibrosing disorders. Current hypothesis suggests that profibrotic cytokines might trigger epigenetic changes which contribute to the persistently activated fibroblast phenotype. In the last years, several epigenetic alterations have been described in SSc and have been linked to different pathogenic aspects of the disease, in particular to aberrant fibroblast activation and tissue fibrosis, but also to vascular manifestations and inflammation. The focus of this review is the current knowledge on epigenetic changes in fibroblast activation in SSc.
EVALuna2:13414